Induction of Parturition in Ewes with dexametasona - ΤΣΑΜΗΣ, Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
I he administration of IS mgr DEXAMETASONA injected on 145 days of gestation in cinteli parturition within 55 h. in ewes. The maximum number of lambing 73,3% was observed between 30 and 48 h. after injection time. The maintime of parturition in the experimental group was 44.26 ± 2,46 h. after corticoid administration, on the contrary the main time of the part uri (ion in the control group was 93.60 ± 9,35 h. Ρ <0.010>. None of the ewes had retention of placenta during parturition. On the contrary the mortality reduced to 0%. against 15,2% of natural partutition, because of the cattlemans continual wa telling for 55/h. during parturitions concentration.